Analysis of the quantum numbers JPC of the X(3872) particle - Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We present an analysis of angular distributions and correlations of the X(3872) particle in the exclusive decay mode X(3872)→J/ψπ+π- with J/ψ→μ+μ-. We use 780pb-1 of data from pp̄ collisions at s=1.96TeV collected with the CDF II detector at the Fermilab Tevatron. We derive constraints on spin, parity, and charge conjugation parity of the X(3872) particle by comparing measured angular distributions of the decay products with predictions for different JPC hypotheses. The assignments JPC=1++ and 2-+ are the only ones consistent with the data. © 2007 The American Physical Society.